Efficient online/offline IBSS protocol using partial discrete logarithm for WSNs. Issue 6 (1st November 2018) - Meshram, Chandrashekhar; Powar, Pournima L.; Obaidat, Mohammad S.; Lee, Cheng‐Chi; Meshram, Sarita Gajbhiye
Abstract : An online/offline identity‐based short signature (IBSS) protocol permits the signer to produce an online IBSS in real time from a precomputed offline IBSS when given a record. Such techniques are especially valuable in resource‐constrained wireless sensor network (WSN) applications. Recently, Meshram et al . presented an UF‐IBSS‐CMA‐protected online/offline IBSS protocol using partial discrete logarithm. In this study, the authors propose an extension of Meshram et al . scheme and compare with other IBSS protocols. The presented offline signing process does not want any private data from the signer. Henceforth, it can be created by any reliable outsider with the private key generation (PKG). This is especially valuable as the base station for a WSN node, performing as a PKG, can produce the offline data and the node does not have to come back to the base station for the re‐establishment of the offline data each time signing is implemented. Also, they demonstrate how the scheme can be extended to allow a single user to sign multiple messages and its implementation on WSN.